Effectiveness of Copaxone in patients with relapsing-remitting multiple sclerosis - V. M. Alifirova; M. A. Titova; A. A. Vereschaka (Бюллетень сибирской медицины)
We investigated the effectiveness of Copaxone in patients with relapsing-remitting multiple sclerosis for 3 and 5 years. Significant improvement found the decrease of the frequency of clinical exacerbations and delay the accumulation of physical disability during treatment period.